Electrochemical synthesis and properties of cadmium selenide sensitised titania nanotubes for photoelectrochemical cells - Ayal, Asmaa Kadim (2017)
Solar energy is an alternative sustainable energy resource that can be harvested using photoelectrochemical cell comprised of inorganic sensitized nanostructured oxide semiconductor electrode. In this work, the electrochemical synthesis, characteristics and photoelectrochemical performance of cadmium selenide (CdSe) sensitized titanium dioxide nanotube arrays (TiO2 NTAs) were studied. TiO2NTAs thin film electrodes were prepared by the anodisation method of titanium foil in a two electrode cell containing NH4F solution. Parameters affecting the morphology,structure and geometry of TiO2NTAs were investigated in three different electrolytic media namely the acidic aqueous solution (NH4F/H2O), mixture of aqueous/organic solution (NH4F/H2O/EG) and an organic solution (NH4F/EG). The characteristics of TiO2NTAs were examined using X-ray diffractometry (XRD), energy dispersive X-ray analysis (EDX), field emission scanning electron microscopy (FESEM), Transmission Electron Microscopy (TEM) and High Resolution Transmission Electron Microscopy (HRTEM) and UV-visible diffuse reflectance spectroscopy (UV-DRS). Meanwhile, the photoelectrochemical responses of TiO2NTAs were investigated using linear sweep photovoltammetry (LSPV). Three electrochemical deposition methods were used to deposit CdSe onto TiO2NTAs by applying the potentiostatic deposition, cyclic voltammetric deposition and pulse electrodeposition methods. CdSe was electrodeposited onto TiO2NTAs from an electrolyte containing CdCl2 and SeO2with Na2SO4as the supporting electrolyte. Cyclic voltammetry was used to select the probable range of the potential for deposition which was found to be from -0.65 V to -1.00 V. Potentiostatic electrodeposition techniques has been carried out at the different potential of deposition, time of deposition, concentration of SeO2, concentration of CdCl2, pH and temperature of annealing. For pulse electrodeposition, the effect of varying deposition potential, deposition time, duty cycle, concentration of SeO2, concentration of CdCl2, pH, and temperature of annealing were studied. The effect of different potential range, scan rate, number of cycles, pH and temperature of annealing were investigated for cyclic voltammeric deposition. X-ray diffraction (XRD) patterns showed that the deposited CdSe onto TiO2NTAs were polycrystalline with hexagonal structure. The photoelectrochemical (PEC) properties of the synthesised films were evaluated using linear sweep photovoltammetry (LSPV) by illuminating the samples intermittently with a halogen lamp (120 V, 300 W) while immersing in 0.01 M Na2S electrolyte. Photocurrent was observed due to the reaction involving generated minority carriers (holes) on the electrode surface. Therefore, the deposited CdSe is an n-type semiconductor in this work. The XRD and PEC results suggested that the suitable electrolyte bath composition for CdSe deposition was 20 mM CdCl2, 5 mM SeO2, and 20 mM Na2SO4. Uniform potentiostatic deposition of CdSe onto TiO2NTAs was obtained at the potential of -0.7 V with the deposition time of 30 minutes at pH 3.0 under the annealing condition of 250 °C in N2 atmosphere for 60 minutes. Meanwhile, pulse electrodeposition involved pulse potential of -0.85 V at 20 minutes of Ton with 50% duty cycle under the annealing condition of 350 °C in N2 atmosphere for 60 minutes. Besides, cyclic voltammetric deposition was conducted at the potential range of -0.60 V to -1.00 V with the scan rate of 5 mV/s for 6 cycles at pH 3.0 under the annealing condition of 250 °C in N2 atmosphere for 60 minutes. It was found that the optical properties of CdSe/TiO2 nanotubes films have direct optical band gap energy values (Eg) in the range of 1.7 eV to 1.84 eV. The morphological property of the prepared samples was examined by field emission scanning electron microscopy (FESEM). The crystallite sizes of CdSe determined from XRD were in between 10.80 for potentiostatic technique, 15.50 nm for pulse electrodeposition and 7.00 nm for cyclic voltammetric deposition. The ratio of Cd:Se was 1:1 as shown in EDXenergy dispersive X-ray analysis. The photoefficiency was evaluated in 0.01 M Na2S under halogen illumination. The CdSe/TiO2 nanotubes film deposited using pulse deposition displayed the best photoefficiency (1.96%) compared to potentiostatic and cyclic voltammetric techniques.